(untitled) - Dalton Tavares Bressane Nielsen (Neotropical Ichthyology, 2013)
Spectrolebias brousseaui is described from a temporary pool from the upper río Mamoré basin, Departamento Santa Cruz, Bolivia. The new species is distinguished from all congeners, by the overall dark blue coloration on the posterior two-thirds of body with bright blue iridescent spots vertically aligned in males. Spectrolebias brousseaui differs from all other species of the genus, except S. filamentosus, for having pelvic fins separated by a space (vs. pelvic fins in contact), long filaments at the tip of the dorsal and anal fins in males (vs. absence of filaments or presence only on dorsal fin in S. semiocellatus and S. inaequipinnatus, or the presence on the anal fin in S. chacoensis), and presence of contact organs on the scales of the flanks in males (vs. absence of contact organs on flanks in all remaining Spectrolebias species). Spectrolebias brousseaui é descrita de uma poça temporária localizada na região superior da bacia do río Mamoré, departamento de Santa Cruz, Bolívia. A espécie nova distingue-se de todos os congêneres pelo padrão de cor azul escuro nos dois terços posteriores do corpo com pontos azuis claros iridescentes alinhados verticalmente em machos. Spectrolebias brousseaui difere das outras espécies do gênero, exceto S. filamentosus, por ter as nadadeiras pélvicas separadas por um espaço (vs. nadadeira pélvicas juntas), longos filamentos nas extremidades das nadadeiras dorsal e anal em machos (vs. ausência de filamentos ou a presença apenas na nadadeira dorsal em S. semiocellatus e S. inaequipinnatus, ou pela presença de filamentos na nadadeira anal em S. chacoensis), e presença de órgão de contato nas escamas do flanco em machos (vs. ausência)